Supply Chain Management, Certificate Management at the Transportation Layer Security in Charge of Security - Tsara Ayuninggati; Eka Purnama Harahap; Mulyati; Raihan Junior (Blockchain Frontier Technology, 2021)
In the public key infrastructure, the certification authority is fully trusted, and the security of the public key infrastructure depends on the trust of the certification authority; however, recent attacks and corruption on the certification authority indicate that the certificate is forged when the certification authority fails . New solutions, blockchain-based public key infrastructure products and registry can repair vulnerabilities in public key infrastructure, especially weaker security systems. Proposals for infrastructure-based public key infrastructure. Public keys are still the target of global attacks. According to the registration of the target victim, it is signed as a temporary public key infrastructure based on the blockchain. High growth rates require permission to use the wallet. To solve this problem, this document introduces an integrated and responsible system for managing security certificates at the transport layer that represents the next generation of public key infrastructure.I merged two new architectures, introduced a new process, and created a registration and CA server. The domain owner has been notified. In supply chain management, the domain certificate signed by the CA is stored on the registration server, and the certificate server and the CA registration server are forwarded to the group that owns the domain. Compared with existing supply chain public key infrastructure products. The above-mentioned blockchain-based public key infrastructure scheme and registry are used for security and governance analysis.